Pengembangan Media Web Genially dalam Pembelajaran Bahasa Arab pada Maharah Siswa SMP Surya Buana Malang - Arieni Alfakhaera; Danial Hilmi; Usfiyatur Rusuly (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the lack of use of interactive learning media in Arabic language learning, resulting in students being less active and less interested in participating in the learning process. Therefore, an Arabic language learning media based on Genially Web was developed to support students' learning skills. This research aims to: (1) understand the process of developing Arabic language learning media based on Genially Web, (2) determine the validity level of the developed media, and (3) assess the effectiveness of using the media in Arabic language learning. This research uses the Research and Development (R&D) method with the ADDIE development model, which includes the stages of Analyze, Design, Development, Implementation, and Evaluation. Data collection techniques were carried out thru observation, interviews, questionnaires, and tests. Product testing uses a pretest-posttest design. The research results show that the Arabic language learning media based on Genially Web was developed with features including a title page, learning objectives, materials for maharah kalam, istima’, qira’ah, and kitabah, practice questions, quizzes, and a developer profile. The validation results show that the media is declared valid with a material expert validation percentage of 91.67% and a media expert validation percentage of 80%. Additionally, the developed media has proven to be effective in learning. This is indicated by the increase in the average student scores from a pretest of 87.56 to a posttest of 95.30. The N-Gain test results obtained an average of 87.55 with a high category, while the Paired Sample T-Test showed a significance value of 0.000 < 0.05, which means there is a significant difference between the pretest and posttest results.